(untitled) (Research, Society and Development, 2022)
Melanoma is responsible for most skin cancer related mortalities, and its best prognosis is related to early diagnosis and treatment. In this sense much has been studied about the treatment of the disease, relating mainly to selective inhibitors of signaling pathways. Therefore, the present review addresses the use of monotherapies of BRAF (vemurafenib and dabrafenib) and MEK (trametinib) inhibitors, the possible combinations between them and other therapeutic options that may be promising to participate on the neoadjuvant and adjuvant treatment with the selective inhibitors, since the main limitations in treatment with these inhibitors is the frequent development of drug resistance mechanisms. In order to obtain the necessary content, a bibliographic review was carried out in the following databases of the Virtual Health Library, PubMed, Scielo and Google Academic, using the following keywords: melanoma, BRAF and MEK inhibitors, dabrafenib monotherapy and vemurafenib, dabrafenib and trametinib combinations, protein disulfide isomerase action, immunotherapy in the treatment of metastatic melanoma. After the information survey it was possible to conclude that dabrafenib + trametinib combination therapy is more advantageous in view of the adverse effects, quality of life and progression free survival of the patient when compared directly to selective chemotherapy monotherapies, and this may be considered for future studies that include, for example, combination with immunotherapy or quercetin, a potential natural inhibitor for PDI.